The Relationship Between Retinol/Retinol Binding Protein 4 ratio, resistin and inflammation in non diabetic obese Indonesian men (Medical Journal of Indonesia, 2010)
Aim To verify the correlation between Retinol/RBP4 Ratio, and resistin with inflammation (represented by hsCRP) in non-diabetic obese Indonesian men Methods This was a cross sectional study using 125 subjects. Measured parameters were retinol, RBP4, resistin, and hsCRP. Correlation between retinol, RBP4, resistin, hsCRP and Retinol/RBP4 Ratio was calculated. Cut off point of hsCRP were classiied as follows: <1 mg/l for low risk of inflammation, 1-3 mg/l for moderate risk, and 3-10 mg/l for high risk (according to CVD risk). The Retinol/RBP4 ratio was dichotomized into high (>0.9) and low ratio (≤0.9). The cross tabulation test was performed to predict the inflammation trends described by Retinol/RBP4 Ratio and resistin. Results Retinol was found strongly correlated with RBP4 and resistin (r=0.53; p<0.01). A positive but not significant correlation was found between resistin and Retinol/RBP4 Ratio with hsCRP. In high ratio group, 17.6% subjects were found with low risk inflammation, 26.4% with moderate risk, and 20.8% with high risk, in low ratio group, 8% subjects were low risk inflammation, 20% moderate risk, and 7.2% high risk. Combination between ratio and resistin showed that in “high ratio and low resistin” group, 12% subjects have low risk of inflammation and 8% have high risk. Meanwhile in “low ratio and high resistin” group, 3.2% subjects were found having low risk and 13.6% high risk of inflammation. Conclusions Combination between Retinol/RBP4 Ratio and resistin showed better description about the inflammation risk in non-diabetic obese subjects compare to the ratio itself. (Med J Indones 2010; 19:57-63) Keywords: Retinol, RBP4, resistin, hsCRP, obesity, inflammation